DIGITAL TRANSFORMATION IN AGRICULTURE IN VIETNAM: TRENDS, OPPORTUNITIES, AND CHALLENGES - Thi Thanh Huyen Pham; Tuan Anh Tran (HUIT Journal of Science, 2025)
Digital transformation is emerging as a crucial driver for enhancing productivity, optimizing value chains, and promoting sustainable development in the agricultural sector. In Vietnam, digital transformation in agriculture has shown promising initial results, particularly in provinces like Lam Dong, An Giang, and the Mekong Delta, with the application of technologies such as IoT, AI, and Blockchain. Leading enterprises like VinEco and Nafoods have pioneered the adoption of digital solutions for supply chain management and product traceability, resulting in increased productivity and added value for agricultural products. However, the transformation process remains fragmented, with significant disparities between large-scale farmers and smallholder farmers. While digitally advanced models thrive in areas with favorable infrastructure and enterprise-driven ecosystems, smallholder farmers still face barriers related to capital, digital literacy, and technology access. By employing theoretical frameworks such as Innovation Diffusion, Absorptive Capacity, Farming Systems, Open Innovation, and Sustainable Development, this study analyzes the driving forces, disparities, and challenges of digital transformation in Vietnamese agriculture. The findings highlight that successful digital transformation requires more than just technology adoption; it necessitates an integrated ecosystem involving the government, enterprises, research institutions, and farmers. Coordinated efforts in improving rural digital infrastructure, enhancing farmers' digital capabilities, and fostering public-private partnerships are essential to ensure that digital transformation becomes a catalyst for inclusive and sustainable agricultural development in Vietnam.